Modelling and Evaluation of Steam Net Control in a Pulp Mill - Arvidsson, Monika; Lindgren, Agnes (My University, 2024)
Abstract In this thesis, modified control strategies are implemented in a simulation environment to evaluate the performance of a steam system in an existing pulp mill. The steam system consists of several pressure headers which are connected to multiple valves. In the existing control system, one controller aims to maintain a pressure set point for each pressure header. A smart split-range strategy, developed by Solvina AB, is used to distribute the signal from a given controller to valves that alter their opening degree according to the control signal. The aim of the presented work was to identify new solutions that change the control of the valves and the control hierarchy of the system to increase energy efficiency while maintaining or improving the system stability. Three different solutions were implemented in the software Dymola. The first solution deals with the opening sequence of non-linear valves. The second and third implementations consider the control sequence of steam excess at a pressure header and the control of the existing accumulator. To evaluate the performance, the steam system was tested by being exposed to three dynamic changes. These changes were a load trip, a load start-up and a partial turbine trip. It was found that there is a trade-off between decreased fuel usage and increased electricity generation. Furthermore, it was seen in some of the simulations that an improved accumulator usage could be achieved, but at the expense of decreased pressure stability, and vice versa.
Keywords: Keywords: Energy Efficiency, Steam Net Control, Split-Range, Control System, Steam Network, Pulp Mill Process, Automatic Control